1995
DOI: 10.1002/bip.360350513
|View full text |Cite
|
Sign up to set email alerts
|

Design of B‐DNA cross‐linking and sequence‐reading molecules

Abstract: We report the design of hybrid molecules to bind in the minor groove of B-DNA, which combine DNA alkylating and cross-linking ability for increased chemotherapeutic efficacy, with sequence specificity, to minimize side effects. Optimal linkage geometries have been determined for the synthesis of bis-anthramycin and anthramycin-netropsin hybrid molecules. Earlier studies on linked drugs have typically been based on molecular mechanics calculations. This work, in contrast, uses the observed crystal structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…These agents have also received considerable attention as DNA anchoring systems for nonspecific DNA cleaving agents such as Fe II −EDTA . Additionally, conjugation to the 5‘-AATT-3‘ minor groove binding agent netropsin has been pursued as a means of enhancing the specificity of DNA modification by anthramycin …”
Section: 83 Pyrrolobenzodiazepine Dimersmentioning
confidence: 99%
“…These agents have also received considerable attention as DNA anchoring systems for nonspecific DNA cleaving agents such as Fe II −EDTA . Additionally, conjugation to the 5‘-AATT-3‘ minor groove binding agent netropsin has been pursued as a means of enhancing the specificity of DNA modification by anthramycin …”
Section: 83 Pyrrolobenzodiazepine Dimersmentioning
confidence: 99%
“…netropsins or lexitropsins together via a short connecting chemical group or linker. Initial design of these linkers involved trial and error and chemical intuition, but for a systematic, computer-based design of linker groups such as that discussed by Walker et al (1995), one must know the precise positioning of drug monomers on the DNA duplex. Even a slight mispositioning of drug will lead to erroneous geometry for the linkers to be synthesized.…”
Section: Dykementioning
confidence: 99%
“…Because the precise alignment of the netropsin molecule on DNA is so critical to systematic drug design, especially the synthesis of bis-linked dimers (Walker et al, 1995), we have reexamined the issue of class I vs class II positioning of the netropsin molecule in its DNA complex. Using the original netropsin/CGCGAATT5BrCGCG data, we have rerefined netropsin both in the class I position presented by Kopka et al (1985a-c) and in the class II alternative reported more recently by Sriram et al (1992).…”
Section: Dykementioning
confidence: 99%
“…The first DNA-interactive anticancer drugs belong to the family of the covalently binding DNA alkylating agents (6,7). In recent years, ligands that bind non-covalently in the minor groove have attracted considerable attention because of their pronounced sequence specificity (8).…”
Section: Introductionmentioning
confidence: 99%